Analisis Manajemen Koleksi dalam Memenuhi Kebutuhan Informasi Pada Perpustakaan Sekolah - Pratama, Bagas Aldi; Zulaikha, Sri Rohyanti; Rifauddin, Machsun (LIBTECH: LIBRARY AND INFORMATION SCIENCE JOURNAL, 2024)
The school library is one of the important facilities in supporting the success of the teaching and learning program. Its main function is to provide learning references for students, teachers and technical personnel at school. Before the information is presented, school librarians manage the library materials through several stages. This study aims to determine the application of SNP Number 12 of 2017 in the collection management section in school libraries.  The research method used a descriptive qualitative approach with data search techniques through observation, interviews, and documentation. The research location is in the library of SMAN 1 Kedungwaru, MAN 2 Tulungagung, and SMKN 1 Rejotangan. The three schools have different focuses according to their respective development focus. The results showed that the implementation of library collection management has not fully met the SNP standard number 12 of 2017. The three libraries have not met the minimum standards for the type and number of collections. The availability of electronic collections and reference collections such as dictionaries is only the library of SMAN 1 Kedungwaru that has met the standards. However, other standards have met the SNP, such as the processing of library materials and weeding activities that are scheduled and carried out routinely once a year, and maintenance of library materials at least once a year.